Oxygen Vacancy-Mediated Interfacial Charge Transfer of Au/ZnO Schottky Heterojunctions for Enhanced UV Photodegradation - Zhufeng Shao; Hui Jia; Yufeng Zhang; Xiujuan Yang; Min Zhong; Chun Chang (International Journal of Photoenergy)
We intend to report an interesting phenomenon related to the different interfacial transfer processes between ellipsoidal-like ZnO (E-ZnO) and rod-like ZnO (R-ZnO) nanoheterojunctions witness by the nanosecond time-resolved transient photoluminescence (NTRT-PL) spectra. Fristly, E-ZnO and R-ZnO nanoarchitectures were fabricated via facilitating the electrochemical route; and then, they decorated it with dispersed Au nanoparticles (NPs) by the methods of ion-sputtering deposition, constituting Au/E-ZnO and Au/R-ZnO Schottky-heterojunction nanocomplex, which is characterized by SEM, XRD, Raman analysis, and UV-vis absorption spectra. Steady-state photoluminescence and NTRT-PL spectra of as-fabricated Au/E-ZnO and Au/R-ZnO nanocomposites were probed for interfacial charge transfer process under 266 nm femtosecond (fs) light irradiation. Simultaneously, a distinct diversification for the NTRT-PL spectra is observed, closely associating with oxygen vacancies (Vo), which is confirmed by X-ray photoelectron spectroscopy (XPS) and electron spin resonance (ESR) spectra. Furthermore, Au NPs act as an “annular bridge” and “transit depot” for interfacial charge transfer through local surface plasmon resonance (LSPR) effect and Schottky barrier, respectively, which is identified by NTRT-PL and time-resolved PL (TRPL) decay spectrum. Moreover, this mechanism is responsible for the enhanced photoelectrochemical (PEC) performances of methyl orange (MO) photodegradation under UV light irradiation.